Hybrid SSA-PSO based intelligent direct sliding-mode control for extracting maximum photovoltaic output power and regulating the DC-bus voltage - AL-Wesabi, Ibrahim; Fang, Zhijian; Farh, Hassan M. Hussein; Dagal, Idriss; Al-Shamma'a, Abdullrahman A.; Al-Shaalan, Abdullah M.; Kai, Yang (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
Photovoltaic (PV) energy has become a considerably more attractive source of power, with costs continually declining. Along with the implementation of this sustainable energy system, the power supply stability should be extensively investigated, particularly in off grid systems where electricity storage becomes a limitation. The performance of the standalone photovoltaic battery system (SPVBS) is mainly reliant on the DC-bus voltage and its capacitor. The shortcomings of utilizing a small film DC-bus capacitor in SPVBS include the instability and low-frequency ripple of DC-bus voltage and the system's dynamic MPPT techniques performance. Therefore, this study proposes a new technique of regulating the various system components that stabilizes the DC-bus voltage, extracts stable output power despite harsh sudden load and radiation fluctuations, and maintains the system's functionality with or without the battery storage system (BSS). The proposed
Keywords: Maximum power; DC-Bus voltage regulation; SSA-PSO; ENERGY MANAGEMENT; FUEL-CELL; CONTROL STRATEGY; MPPT CONTROLLER; POINT TRACKING; SYSTEMS; OPTIMIZATION; DESIGN; CONVERTER; ALGORITHM; Chemistry; Electrochemistry; Energy & Fuels